Contact Dermatitis Due to Para-Phenylenediamine (PPD) on a Temporal Tattoo With Henna. Cross Reaction to Azoic Dyes - Di Prisco, María Cristina; Puig, Lluis; Alomar, Agustín (Investigación Clínica, 2009)
Henna is used as a hair dye and to make temporary tattoos on the skin. It is usually mixed with p-phenylendiamine (PPD) to increase colour intensity and to reduce the time of fixation on the skin proteins. PPD can cross react with azoic dyes which are used as textile dyes. We studied a patient with skin eczema in the area of a henna temporary tattoo. The epicutaneous tests performed with the standard Trolab and Chemotecnique® hair dressing and textile batteries, showed positive results to PPD, p-toluendiamine, 5-4aminophenol, Yellow 3, Orange Red and Red 1, and negative results to three types of henna. The eczema in this patient was due to sensitisation to PPD on a henna tattoo with cross reaction to azoic dyes. The recent fashion of applying temporal tattoos in occidental countries may produce an increase in the frequency of contact dermatitis due to henna mixtures with cross- reaction to related compounds and possibly producing permanent skin changes